Emerging experimental strategies for studies on inhomogeneous nanomaterials: Exploring electronics, atomic structure and properties by synchrotron X-Ray-based techniques - Requejo, Felix Gregorio (2020)
Through representative examples, we illustrate the strategic value of synchrotron X-ray-based techniques for nanomaterial characterization, especially for inhomogeneous nanomaterials. These examples are used to describe opportunities, motivations for new questions and possible reexamination of older topics, not only due to the proven success of the scientific instrumentation, but also because the extraordinary specific advantages offered by the new X-ray micro and nanoprobes techniques.